Cytochrome o3 hemepocket relaxation subsequent to carbon monoxide photolysis from fully reduced and mixed valence cytochrome bo3 oxidase - Kreszowski, Douglas; Babcock, Gerald T.; Varotsis, Constantinos (My University, 1996)
Time-resolved resonance Raman spectroscopy has been used to probe the structural dynamics at the heme o3 proximal and distal sites subsequent to carbon monoxide photolysis from fully reduced and CO mixed-valence cytochrome bo3 ubiquinol oxidase. The spectra of the transient species exhibit structural differences relative to the equilibrium geometry of heme o3. The most significant of these is a shift of 4 cm-1 to higher frequency of the 208-cm-1 mode in the transient species. Our results indicate that the 208-cm-1 mode observed in the equilibrium-reduced heme o3, which was recently assigned to the Fe2+-His of heme o3, is located at 212 cm-1 in the 10-ns spectrum. The behavior of the Fe2+-His mode in the photolytic transients of cytochrome bo3 indicates that at times ∼ 10 μs subsequent to CO photolysis the proximal heme o3 geometry is fully relaxed. The rate of relaxation of heme o3 is similar to that observed in the heme o3 transients of cytochrome aa3 oxidase. At later times (td > 100 μs) the appearance of the 212-cm-1 peak signals the onset of CO rebinding to the previously photolyzed heme o3. Neither the fully reduced nor the mixed-valence species exhibits geminate ligand recombination on a 10-ns time scale. Both species, however, display relaxation of ν(Fe-His) to its equilibrium position, at 208 cm-1, on a 10-μs time scale, and ligand rebinding on a 200-μs time scale. Our results indicate that the rate of relaxation of heme o3 and the CO rebinding to heme o3 are independent of the redox state of the low-spin heme b. Collectively, the transient intermediates of heme o3 suggest significant alterations in the nature of the heme-protein dynamics between cytochrome c aa3 oxidase and quinol cytochrome bo3 oxidase resulting from specific structural differences within their respective proximal and distal hemepockets
Keywords: Cytochrome; Carbon monoxide; Photochemistry; Cytochrome oxidase; Raman spectroscopy; Structural dynamics; Heme